Analisis Kebijakan Pemberantasan Narkotika Di Indonesia Dalam Perspektif Kriminologi - Bahaduri, Laksa Bayu; Susanti, Vinita (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
Illicit Trafficking and Abuse of Narcotics and illegal drugs at this time can be said to be an extraordinary crime and get a strong spotlight in various circles, both in society, government and even internationally. This is because the negative impact that can be caused by the abuse of Narcotics is very large and detrimental in terms of health, economy, social, culture and even aspects of national security. Policies are directly or indirectly influenced from international and national aspects in the prevention and eradication of drugs, there are still some weaknesses in government policies in the overall criminal justice system, especially the correctional system in the field of eradication in dealing with narcotics abuse and illicit trafficking. This research is a type of literature study research by looking for data and information references and theories that are relevant to the cases or problems found. The conclusion of this study is a model of a centralized penitentiary specifically for narcotics convicts supported by the participation of relevant stakeholders in its implementation and supervision